2012
DOI: 10.1088/0256-307x/29/9/098402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminium Nanoparticles on the Performance of Bulk Heterojunction Organic Solar Cells

Abstract: Al nanoparticles (NPs) are incorporated in the active layers to enhance the performance of organic solar cells (OSCs). The improved short circuit current Jsc and power conversion efficiency (PCE) for OSCs with Al NPs are observed. A final PCE of 3.66wt% is achieved, which is an improvement of more than 30wt% compared to a standard cell with a PCE of 2.84wt%. When the mass of Al NPs is 10wt% of OSCs, the device performance is best. The optical performance of OSCs reveals that the absorption from sunlight increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A prospective effort made by researchers for improving conversion efficiency of OSCs is the incorporation of metal nanoparticles (NPs) in different parts of solar cell architecture. The metal NPs have been incorporated in solar cell active layer blend [6], in the buffer layer [7], or at the interface between buffer layer and indium tin oxide (ITO) electrode [8]. Specifically, the incorporation of metallic NPs in different solar cell layers can enhance the absorption of the light propagating in these layers by two mechanisms: a near-field enhancement and an increasing of the forward scattering cross section [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective effort made by researchers for improving conversion efficiency of OSCs is the incorporation of metal nanoparticles (NPs) in different parts of solar cell architecture. The metal NPs have been incorporated in solar cell active layer blend [6], in the buffer layer [7], or at the interface between buffer layer and indium tin oxide (ITO) electrode [8]. Specifically, the incorporation of metallic NPs in different solar cell layers can enhance the absorption of the light propagating in these layers by two mechanisms: a near-field enhancement and an increasing of the forward scattering cross section [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Al NPs are incorporated inside solar cell active layer at different concentrations of the NPs in the active layer and different ultrasonication times at which the Al NPs are prepared using ultrasonic ablation technique. The Al NPs are blended in active layer of the common solar cell based on poly(3-hexylthiophene) (P3HT), as a donor polymer, and [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM), as an acceptor. The solar cell with the configuration ITO/poly(3,4-ethylene dioxythiophene)-blend-poly(styrene sulfonate) (PEDOT:PSS)/P3HT:PCBM-Al NPs/Al, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the efficiency of organic photovoltaic cells, many researchers have improved the performance of cells from different aspects. For instance, LiF or ZnO and other cathode modified materials were added between the active layer and cathode [3,4]; isopropanol was taken to process the buffer layer of PEDOT:PSS, making it have high conductivity and good surface morphology [5], the cell performance was improved through selection of optimal annealing temperature and time, and the optimal active layer thickness [6], Zhang et al [7] introduced the mixed solvent to change the film surface morphologies and enhance the device properties; some researchers enhanced the effect by using the resonance of nanoparticles and improved the cell efficiency by adding nanoparticles to the active layer to improve adsorption [8]. Hu et al [9] found that the addition of addictive 1 and 8-diiodomethane octane into the active layer solution could optimize the separation degree of active layers of polymer solar cells, further improving the absorption of devices for the near infrared spectrum and the short-circuit current density, with the energy conversion efficiency increased by 17% or so.…”
Section: Introductionmentioning
confidence: 99%
“…The PSC performance can be improved by modifying the electrodes: for example, a LiF, ZnO, or poly(ethylene oxide) (PEO) layer can be added between the active layer and cathode to modify the cathode [5][6][7]. Doping with metal nanoparticles is a method of increasing light absorption that has been used in the manufacturing of solar cells [8,9]. Mixed solvents can be used to improve the solar cell performance [10].…”
Section: Introductionmentioning
confidence: 99%